ANALISIS PENGARUH WAKTU TUNGGU DAN KEPUASAN TERHADAP MINAT BERKUNJUNG KEMBALI PASIEN DI PUSKESMAS EYAT MAYANG KABUPATEN LOMBOK BARAT TAHUN 2024 - Nisa, Hairun; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Lale Ajeng Khalifatun Wardani (Nusadaya Journal of Multidiciplinary Studies, 2024)
This study was motivated by the fluctuation in the number of general patient visits to the Eyat Mayang Community Health Center in West Lombok Regency over the past five years, indicating potential problems in service quality. The decrease in the number of visits from 3432 in 2022 to 1966 in 2024 indicates the need for an evaluation of the factors influencing patients' willingness to return to the health center. Two important factors suspected to have an influence are waiting time and patient satisfaction. This study aims to analyze the influence of these two factors on patients' willingness to return for visits. The objectives of this research are to analyze the partial influence of waiting time on patient return visits, to analyze the partial influence of patient satisfaction on return visits, and to analyze the simultaneous influence of waiting time and patient satisfaction on return visits. This study uses a quantitative method with an associative approach. A sample of 30 general patients at the Eyat Mayang Community Health Center was selected using accidental sampling. Data were collected using a questionnaire measuring waiting time, patient satisfaction, and willingness to return for visits. Data analysis was performed using multiple linear regression, preceded by classical assumption tests (normality, multicollinearity, and heteroscedasticity). Hypothesis testing was performed using the t-test (partial), F-test (simultaneous), and R-square test. Descriptive analysis shows that the majority of respondents were aged 17-25 years, had a high school education, and were male. The results of the multiple linear regression test show that the overall regression model is not significant (p-value > 0.05). Although the R-square of 0.481 shows that waiting time and satisfaction explain 48.1% of the variance in return visits, the influence of these two variables, both partially and simultaneously, on patient return visits is not statistically significant. This indicates that there are other factors that more dominantly influence patients' willingness to return to the Eyat Mayang Community Health Center. Classical assumption tests were met.